Collection and storage of human white blood cells for analysis of DNA damage and repair activity using the comet assay in molecular epidemiology studies. (23rd March 2021) - Møller, Peter; Bankoglu, Ezgi Eyluel; Stopper, Helga; Giovannelli, Lisa; Ladeira, Carina; Koppen, Gudrun; Gajski, Goran; Collins, Andrew; Valdiglesias, Vanessa; Laffon, Blanca; Boutet-Robinet, Elisa; Perdry, Hervé; et al.
Abstract: DNA damage and repair activity are often assessed in blood samples from humans in different types of molecular epidemiology studies. However, it is not always feasible to analyse the samples on the day of collection without any type of storage. For instance, certain studies use repeated sampling of cells from the same subject or samples from different subjects collected at different time-points, and it is desirable to analyse all these samples in the same comet assay experiment. In addition, flawless comet assay analyses on frozen samples open up the possibility of using this technique on biobank material. In this article we discuss the use of cryopreserved peripheral blood mononuclear cells (PBMCs), buffy coat (BC) and whole blood (WB) for analysis of DNA damage and repair using the comet assay. The published literature and the authors' experiences indicate that various types of blood samples can be cryopreserved with only a minor effect on the basal level of DNA damage. There is evidence to suggest that WB and PBMCs can be cryopreserved for several years without much effect on the level of DNA damage. However, care should be taken when cryopreserving WB and BCs. It is possible to use either fresh or frozen samples of blood cells, but results from fresh and frozen cells should not be used in the same dataset. The article outlines detailed protocols for the cryopreservation of PBMCs, BCs and WB samples.